Supporting self‐management after traumatic brain injury: Codesign and evaluation of a new intervention across a trauma pathway - Petra Mäkelä (Health Expectations, 2019)
Abstract Background Supported self‐management (SSM) is a recognized approach for people with long‐term conditions but, despite the prevalence of unmet needs, little is known about its role for people with traumatic brain injury (TBI). Objectives To codesign an SSM intervention with people with TBI and evaluate feasibility of implementation through multidisciplinary staff across a trauma pathway. Setting and participants People who had previously been admitted to a Major Trauma Centre following TBI and family members participated in a series of codesign activities. Staff attended SSM workshops and used the intervention with patients in acute and rehabilitation settings. Methods We used Normalization Process Theory constructs to guide and interpret implementation. Knowledge, beliefs and confidence of staff in SSM were assessed through pre‐ and post‐training questionnaires, and staff, patients' and families' experiences were explored through semi‐structured interviews. Qualitative data were analysed thematically, and clinical measures were mapped against a matched sample. Results Codesigned resources were created and used within an SSM approach for which 110 staff participated in training. Evaluation demonstrated significant differences in staff SSM confidence and skills, following training. Qualitative evaluation revealed adoption by staff, and patients' and families' experiences of using the resources. Challenges included reaching staff across complex pathways to achieve collective implementation. Conclusion This is the first project to demonstrate feasibility of SSM for people after TBI starting in an acute trauma setting. Through an open approach to codesign with a marginalized group, the SSM resources were valued by them and held meaning and relevance for staff.